A Diagnosis of Brazilian Shipbuilding Industry on the Basis of Methodology for an Analysis of Sectorial Systems of Innovation - de Araujo,Fernando Oliveira (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2011)
A recent resumption of Brazilian shipbuilding industry, driven by the purchasing power of the state, has presented controversial opinions concerning its effective contribution to, in the first instance, the innovation and competitiveness in the sector and secondly, for Brazilian development. The present study, conducted between November 2009 and May 2011, analyses the said industry from a methodology based on an approach of system sectors of innovation, seeking to highlight the existence and intensity of relationships between the main organizations and institutions, which are members of the industry, in addition to verifying the individual contributions of each of the stakeholders to the industrial competitiveness. As a result of the study, an accurate diagnosis is presented concerning the main aspects to be prioritized through the Brazilian shipbuilding industry, in addition to reviews of proposals of scientific and industrial policies directed towards the said industry, specifically as regards the granting of public funds for research and development demands be revised, as should be aligned to the real needs of the country and the productive sector.